The genetic variability and evolution of red-spotted grouper nervous necrosis virus quasispecies can be associated with its virulence - Ortega-del Campo, Sergio; Díaz-Martínez, Luis; Moreno, Patricia; García-Rosado, Esther; Alonso, M. Carmen; Béjar, Julia; Grande-Pérez, Ana (Frontiers in Microbiology, 2023)
Nervous necrosis virus, NNV, is a neurotropic virus that causes viral nervous necrosis disease in a wide range of fish species, including European sea bass (Dicentrarchus labrax). NNV has a bisegmented (+) ssRNA genome consisting of RNA1, which encodes the RNA polymerase, and RNA2, encoding the capsid protein. The most prevalent NNV species in sea bass is red-spotted grouper nervous necrosis virus (RGNNV), causing high mortality in larvae and juveniles. Reverse genetics studies have associated amino acid 270 of the RGNNV capsid protein with RGNNV virulence in sea bass. NNV infection generates quasispecies and reassortants able to adapt to various selective pressures, such as host immune response or switching between host species. To better understand the variability of RGNNV populations and their association with RGNNV virulence, sea bass specimens were infected with two RGNNV recombinant viruses, a wild-type, rDl956, highly virulent to sea bass, and a single-mutant virus, Mut270Dl965, less virulent to this host. Both viral genome segments were quantified in brain by RT-qPCR, and genetic variability of whole-genome quasispecies was studied by Next Generation Sequencing (NGS). Copies of RNA1 and RNA2 in brains of fish infected with the low virulent virus were 1000-fold lower than those in brains of fish infected with the virulent virus. In addition, differences between the two experimental groups in the Ts/Tv ratio, recombination frequency and genetic heterogeneity of the mutant spectra in the RNA2 segment were found. These results show that the entire quasispecies of a bisegmented RNA virus changes as a consequence of a single point mutation in the consensus sequence of one of its segments. Sea bream (Sparus aurata) is an asymptomatic carrier for RGNNV, thus rDl965 is considered a low-virulence isolate in this species. To assess whether the quasispecies characteristics of rDl965 were conserved in another host showing different susceptibility, juvenile sea bream were infected with rDl965 and analyzed as above described. Interestingly, both viral load and genetic variability of rDl965 in seabream were similar to those of Mut270Dl965 in sea bass. This result suggests that the genetic variability and evolution of RGNNV mutant spectra may be associated with its virulence.